Kajian Transportasi Laut pada Era New Normal Di Kabupaten Bombana - Ruhimat, Iman; Lakawa, Irwan; Sufrianto, Sufrianto (Universitas Sulawesi Tenggara, 2021)
This study aims to investigate sea transportation in the new normal era in Bombana Regency, especially at Kasipute Port. This study includes the number of ships operated, the number of passengers departed and arrived at Kasipute Port, and analyzing the service performance of the Kasipute Port before and during the new normal era. The research method was carried out by collecting secondary data as data recapitulation of ships operated and the volume of passengers departed and arrived at the Kasipute Port at the Office of the Bombana Regency Harbormaster then primary data was get by interviewed passengers (respondents) and filling out questionnaires. It carried service quality analysis using Importance Performance Analysis (IPA). The results showed that during the new normal era, the number of ships operated experienced the highest decline reaching 58% in May 2020. Meanwhile, the largest percentage decrease of passengers during the new normal era was 85% for departed passengers and 77% for passengers arrived at Kasipute port in May 2020. The decline in the number of ships and passengers that occurred during the new normal era was partly due to the PSBB imposed by the Bombana Regency Government since April 2020, so it limited the movement of people using the marine transportation mode. Based on the results of the service quality analysis, the priority factors in improving service performance before the new normal era at Kasipute Port are the comfort of the ship (E1), cleanliness of the ship (C2), and the time of departure of the ship (D1), while the priority factors in improving service performance during the new normal era is the provision of masks by the port (E3), ship cleanliness (C2), ship departure time (D1) and ship comfort (E1).